Self-Reported Rates of Adherence to Aspirin Prescribed as an Antithrombotic Therapy Following Postoperative Total Joint Replacement. (July 2017) - Wittig-Wells, Deborah; Shapiro, Susan; Higgins, Melinda; Samms-McPherson, Jacqueline; Winterboer, Donald Shane; Johnson, Ifeya; Carter, Jessica; Jacob, Ani
Abstract : BACKGROUND: Patients may not understand the importance of medication adherence when discharged with aspirin (ASA) as an anticoagulant for venous thromboembolism (VTE) prophylaxis after joint replacement surgery. PURPOSE: The purpose of this study was to examine self-reported rates of adherence to postoperative use of ASA for VTE prophylaxis. METHODS: This was an exploratory, descriptive study using a convenience sample of 99 participants. Adherence was measured with a 4-question self-reporting tool. RESULTS: Thirty-seven percent were male and 76% were Caucasian, and median age was 63 years. Ninety-two percent had the dosage correct, 76% knew how long to take the medication, and 100% of the sample was still taking the ASA; 40% had forgotten to take 1 or more doses of the medication. No associations were noted. Overall compliance was 44%. CONCLUSION: A significant number missed 1 or more doses. This is an opportunity for nurses to work with patients on innovative ways to improve adherence.